Suscetibilidade de cultivares de soja ao nematoide das lesões radiculares - de Brida, Andressa Lima [UNESP]; Correia, Érika Cristina Souza da Silva [UNESP]; Wilcken, Silvia Renata Siciliano [UNESP] (FapUNIFESP (SciELO), 2017)
Root lesion nematodes, Pratylenchus brachyurus, have caused significant losses in soybean, especially in regions of the Midwest of Brazil. Due to the current importance of this nematode in soybean growing areas and the limited availability of resistant genotypes in Brazil, this experiment was conducted in greenhouse in order to evaluate the reaction of eight soybean genotypes (‘CD 202'; ‘CD 215'; ‘CD 239'; ‘CD 226 RR’; ‘CD 231 RR’; ‘CD 235 RR’; ‘BRS 1841 and ‘BRS 283') to P. brachyurus. The experimental design was completely randomized with eight repetitions. The initial population density (Ip) used was 200 specimens/plant. The final population (Fp) was obtained by extraction of nematodes from the roots and quantified 90 days after inoculation. All soybean genotypes were susceptible to P. brachyurus, but to different degrees, RF between 1.24 and 2.80.
Susceptibility of soybean cultivars to the root lesion nematode
Keywords: Genetic resistance; Glycine max; Pratylenchus brachyurus